Cilvēka Dabas Ambivalence: Ambivalence of Human Nature. - Kamergrauzis, Normunds (Cel̜š, 2017)
The interpretation of human nature and moral possibilities has profound implications for any ethical theory. These differences also imply consequent differences concerning the content of the ethical theory. For this reason, a view on human nature is of prime importance for ethical reflection. The realistic view of human nature, and the consequent assessment of human moral possibilities as exemplified by Reinhold Niebuhr and further developed within a tradition of Christian realism, one sees that those insights which contribute to ongoing ethical reflection derive from already established moral convictions. The argument shows the relevance of the realistic assessment of human moral possibilities for Christian theology and ethics today.